How do you differentiate #f(x)=1/cossqrt(1/x)# using the chain rule?

Answer 1

#-(sec(1/sqrt(x)) tan(1/sqrt(x)))/(2sqrt(x^3)) #

The chain rule is used whenever there are functions of functions. In other words, when you have a function of the form;

#f(x)=g(h(x))#

The chain rule tells us that the derivative of this function is;

#f'(x)=g'(h(x))*h'(x)#

The first step to using the chain rule is to identify the separate functions. Lets start by rewriting the given function to make the component functions easier to identify.

#1/cos(sqrt(1/x)) = cos^-1((1/x)^(1/2))=cos^-1(x^(-1/2))#

Now we have a function of the form;

#f(g(h(x)))#

Where;

#f(x)=x^-1# #g(x)=cosx# #h(x)=x^(-1/2)#

You can see that if you work backwards plugging these functions into each other, you get the original function back.

#f(g(h(x)))=f(g(x^(-1/2)))) = f(cos(x^(-1/2))) = cos^-1(x^(-1/2))#

We can take the derivative of each of these component functions to get;

#f'(x)=-x^-2# #g'(x)=-sinx# #h'(x)=-x^(-3/2)/2#

Now we apply the chain rule to our function.

#d/(dx)cos^-1(x^(-1/2))=-cos^-2(x^(-1/2))d/dx cos(x^(-1/2))#

Apply the chain rule again.

#=-cos^-2(x^(-1/2))(-sin(x^(-1/2)))d/dx x^(-1/2)#

Take the last derivative.

#=-cos^-2(x^(-1/2))(-sin(x^(-1/2)))( -x^(-3/2)/2)#

Simplify.

#=-(sec(1/sqrt(x)) tan(1/sqrt(x)))/(2sqrt(x^3)) #
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To differentiate ( f(x) = \frac{1}{\cos(\sqrt{1/x})} ) using the chain rule, you need to recognize that it is composed of two functions: the outer function ( g(u) = \frac{1}{\cos(u)} ) and the inner function ( u(x) = \sqrt{1/x} ).

First, find the derivative of the inner function:

[ u'(x) = \frac{d}{dx}(\sqrt{1/x}) ]

[ = \frac{d}{dx}(x^{-1/2}) ]

[ = -\frac{1}{2}x^{-3/2} ]

Next, find the derivative of the outer function with respect to its variable:

[ g'(u) = \frac{d}{du}(\frac{1}{\cos(u)}) ]

[ = -\frac{\sin(u)}{\cos^2(u)} ]

Now, apply the chain rule:

[ \frac{d}{dx}(\frac{1}{\cos(\sqrt{1/x})}) = g'(u) \cdot u'(x) ]

[ = -\frac{\sin(\sqrt{1/x})}{\cos^2(\sqrt{1/x})} \cdot (-\frac{1}{2}x^{-3/2}) ]

[ = \frac{\sin(\sqrt{1/x})}{2x^{-3/2}\cos^2(\sqrt{1/x})} ]

So, the derivative of ( f(x) ) with respect to ( x ) using the chain rule is:

[ \frac{\sin(\sqrt{1/x})}{2x^{-3/2}\cos^2(\sqrt{1/x})} ]

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7